Profil Usaha Kuliner Kios Golden Di Kota Manado - Babuno, Novia Pebriarni; Dumais, Joachim Noch Karel; Rumagit, Grace Adonia Josephine (Sam Ratulangi University, 2023)
This study aims to describe the profile of the kiosk business of Golden Kota Manado Jl. Walanda Maramis, Pinaesaan, Manado for three months in a particular week. This research was conducted at Goden Manado Kiosk within three months, namely from July 2022 to September 2022 from preparation to preparation of research reports. The data used are primary and secondary data obtained by direct interviews with Golden kiosk business owners. The data analysis used in this research is to determine the profile/characteristics of the Golden kiosk business in Manado City, analyzed descriptively using tables. The results showed that the Golden kiosk as a culinary business was able to survive until now with the business concept owned by the business owner, namely